A Study on the Need for Human Resource – With Specific Reference to the Manufacturing Sector - et al., Mrs. V. Renuka (International Journal of Advanced Science and Technology, 2019)
The new economic paradigm is characterized by speed, innovation, quality and customer satisfaction. The focus has shifted from tangible to intangible assets, especially on human capital and its effective coalition with the overall organizational strategy. The entire system of measuring HR’s contribution to the organization’s success needs to change to reflect the demands of succeeding in the new competitive economy.